Combined immunotherapy with dendritic cells and cytokine-induced killer cells for solid tumors: a systematic review and meta-analysis of randomized controlled trials - Wendi Jiang; Zhongda Wang; Qinghuizi Luo; Zhe Dai; Jialong Zhu; Xiaoyue Tao; Yiyang Xie; Yuanyang Du; Longwei Jiang; Xiaoyuan Chu; Gongbo Fu; Zengjie Lei (Journal of Translational Medicine)
Abstract Background Immunotherapy utilizing dendritic cells (DCs) and cytokine-induced killer (CIK) cells is a promising treatment approach for solid tumors. This systematic review and meta-analysis aimed to evaluate the efficacy and safety of DC-CIK immunotherapy by assessing overall survival, progression-free survival, overall response rate, disease control rate, and adverse events in relevant randomized controlled trials. The results of this analysis will contribute to optimizing treatment strategies and improving cancer immunotherapy outcomes. Method This systematic review and meta-analysis adhered to PRISMA guidelines. A comprehensive search was conducted on multiple databases for RCTs studying the combination of DC-CIK immunotherapy for solid tumors. Inclusion criteria were RCTs comparing DC-CIK immunotherapy with control therapy and reporting OS, PFS, ORR, or DCR. Two authors independently performed study selection and data extraction, with disagreements resolved through consensus or consultation with a third reviewer. Extracted data included study characteristics, participant information, interventions, outcomes, and quality assessment. Statistical analysis was performed using Review Manager and Stata software. Heterogeneity was assessed using chi-square and I-squared statistics. Sensitivity analysis and assessment of publication bias were planned. Results A total of 1013 records were initially retrieved, and after a thorough screening process, 13 randomized controlled trials (RCTs) were included in the meta-analysis. These studies involved a total of 1443 patients, with 730 receiving DC-CIK immunotherapy and 713 in the control groups. The included studies covered various cancer types, with the majority conducted in mainland China. The meta-analysis showed that DC-CIK immunotherapy was associated with improved overall survival (OS) and progression-free survival (PFS) compared to control therapy. Furthermore, DC-CIK immunotherapy demonstrated higher overall response rate (ORR) and disease control rate (DCR) compared to non-DC-CIK therapy. Adverse events were reported in both groups, with fever being more common in the DC-CIK immunotherapy group and bone marrow suppression and gastrointestinal reactions more common in the control group. Sensitivity analyses confirmed the stability of the results, while publication bias was observed for PFS and fever. Conclusions DC-CIK immunotherapy shows promising efficacy and safety for solid tumors, improving survival rates and response rates. Further research is needed to optimize treatment regimens and identify predictive factors.